المدخل إلى علم العلل ومبادئ النقد الحديثي = Introduction to the study of `Ilal and the principles of hadith criticism - Jamil, Khairil Husaini (2019)
The paper consists of an introductory section and pages from several works in the subject of `ilal (hidden flaws of hadith) produced by classical and medieval critics of hadith.